. Comparison of Denosumab versus Zoledronic acid on serum bone alkaline phosphatase (BAP), total procollagen type 1 amino-terminal propeptide (TP1NP), bone gamma carboxy-glutamic acid containing proteins (BGP), and β isomer of C-terminal telopeptide of ty: serum bone alkaline phosphatase (BAP), total procollagen type 1 amino-terminal propeptide (TP1NP), bone gamma carboxy-glutamic acid containing proteins (BGP), and β isomer of C-terminal telopeptide of type I collagen (β-CTX) - Meng, Jiayin (Journal of Medical Biochemistry, 2024)
Background/aim: To compare the efficacy of Denosumab (DEN) versus Zoledronic acid (ZOL) in treating patients with osteoporotic vertebral compression fractures (OVCF) after percutaneous kyphoplasty (PKP). Materials and methods:In this study, 128 OVCF patients who underwent PKP in our hospital from June 2020 to August 2023 were selected and randomized into a DEN group treated with DEN and a ZOL group treated with ZOL. Bone mineral density (BMD), bone metabolism, pain, and lumbar mobility were compared between the two groups before and after treatment, and the anterior vertebral height and local kyphotic angle were measured. Finally, the one-year re-fracture rate and treatment cost were counted. Results: The two groups showed no notable difference in pain, lumbar mobility, anterior vertebral height, and local kyphotic angle after treatment (P>0.05). BMD was higher in DEN group at 6 and 12 months after treatment, while β isomer of C-terminal telopeptide of type I collagen (β-CTX) was lower (P0.05), while the total treatment cost was lower in DEN group compared with ZOL group (P
Keywords: Osteoporotic vertebral compression fractures, serum bone alkaline phosphatase (BAP), total procollagen type 1 amino-terminal propeptide (TP1NP), bone gamma carboxy-glutamic acid containing proteins (BGP), Denosumab, Zoledronic acid, Bone mineral density